Common and uncommon imaging features of abdominal tuberculosis. Issue 3 (1st April 2019) - Gupta, Pankaj; Kumar, Suresh; Sharma, Vishal; Mandavdhare, Harshal; Dhaka, Narender; Sinha, Saroj K; Dutta, Usha; Kochhar, Rakesh
Summary: Despite the advances in the medical care, tuberculosis (TB) still remains an important health problem. This is particularly relevant to the developing countries as well as the immunocompromised population in the developed world. Multidrug resistance poses another challenge and may be responsible for increasing incidence of TB, to some extent. The respiratory system is the most commonly involved, although any organ system may be affected. Abdominal involvement occurs in 11–12% of the patients with extrapulmonary TB. The clinical features of abdominal TB are nonspecific. Imaging plays an important role in the diagnosis of abdominal TB. Although a few imaging features strongly favour the possibility of TB, abdominal TB is a greater masquerader. In this review, we highlight the entire spectrum of the manifestations of abdominal tuberculosis (excluding the genitourinary involvement) with an emphasis on imaging findings.